Inflammation of the thoracolumbar fascia excites and sensitizes rat dorsal horn neurons - Hoheisel, Ulrich; Mense, Siegfried (European journal of pain, 2015)
Background: Recent data show that the thoracolumbar fascia can be a source of pain. However, the spinal neuronal mechanisms underlying pain from a pathologically altered fascia are unknown. The present study aimed at finding out how dorsal horn neurons react to input from a chronically inflamed thoracolumbar fascia. Methods: Recordings from rat dorsal horn neurons were made in the spinal segment L3. Twelve days before the recordings, the thoracolumbar fascia was inflamed by injection of complete Freund's adjuvant. Control animals received an injection of isotonic saline. In addition, behavioural experiments were carried out. Results: Neurons in the spinal segment L3 do not normally receive input from the fascia, but 11.1% of the neurons did when the fascia was inflamed. Compared with control, the proportion of neurons having input from all deep somatic tissues rose from 10.8% to 33.3% (p < 0.02). Moreover, many neurons acquired new deep receptive fields, most of which were located in the hindlimb (p < 0.04). Surprisingly, the pressure pain threshold of the inflamed rats did not change, but they showed a reduction in exploratory activity. Conclusions: One of the prominent findings was the appearance of new receptive fields in deep tissues of the hindlimb. Together with the expansion of the spinal target region of fascia afferents into the segment L3, the appearance of new receptive fields is a possible explanation for the spread of pain in patients with non-specific low back pain.
Gesehen am 30.11.2018